2002
DOI: 10.1126/science.1074972
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Vesicles

Abstract: Vesicles are microscopic sacs that enclose a volume with a molecularly thin membrane. The membranes are generally self-directed assemblies of amphiphilic molecules with a dual hydrophilic-hydrophobic character. Biological amphiphiles form vesicles central to cell function and are principally lipids of molecular weight less than 1 kilodalton. Block copolymers that mimic lipid amphiphilicity can also self-assemble into vesicles in dilute solution, but polymer molecular weights can be orders of magnitude greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

66
3,188
1
28

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 3,491 publications
(3,283 citation statements)
references
References 47 publications
66
3,188
1
28
Order By: Relevance
“…These screening experiments also revealed that ELP BC s with a hydrophilic-tohydrophobic ratio between 1:2 and 2:1 formed nanoparticles (1:2 ≤ ratio ≤ 2:1). This lower threshold of a 1:2 ratio is similar to an f value of 33%, which was shown by Discher et al 36 to form vesicles. Increasing the hydrophilic-to-hydrophobic ratio above 1:2 also resulted in nanoparticle formation, analogous to Discher's findings36.…”
Section: Thermal Properties Of Elp Bc Ssupporting
confidence: 84%
See 1 more Smart Citation
“…These screening experiments also revealed that ELP BC s with a hydrophilic-tohydrophobic ratio between 1:2 and 2:1 formed nanoparticles (1:2 ≤ ratio ≤ 2:1). This lower threshold of a 1:2 ratio is similar to an f value of 33%, which was shown by Discher et al 36 to form vesicles. Increasing the hydrophilic-to-hydrophobic ratio above 1:2 also resulted in nanoparticle formation, analogous to Discher's findings36.…”
Section: Thermal Properties Of Elp Bc Ssupporting
confidence: 84%
“…In addition, the size of the micelle was controlled by both the total length of the ELP BC and the hydrophilic-to-hydrophobic block ratio supported by the models of Israelachvili et al 42 and Discher et al 36 . For example, increasing the total length while maintaining a constant block ratio increased the micelle size from 29.1 nm for ELP-64/60 (length = 120) to 36.6 nm for ELP-96/90 (length = 180).…”
Section: Light Scattering Of Elp Bc Smentioning
confidence: 96%
“…Synthetic polymers are showing great promise 11 particularly in recent years where liposome and polymer technology have merged in the design of self-assembling membrane-enclosed structures comprised of block copolymers called polymersomes 12,13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Advances in polymer synthesis techniques have enabled polymers to be designed with optimum properties for drug delivery including high molecular weights, enhanced stability, side chain functionality and more importantly, responsiveness [12][13][14]16 .…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved using transmembrane proteins with the appropriate reaction centers able to catalyse several reactions simultaneously (two in our example). Potential scenarios might use polymer vesicles instead of liposomes (Discher and Eisenberg, 2002). After cellular division, each daughter cell has only one metabolic center.…”
Section: Article In Pressmentioning
confidence: 99%